Walter the Chancellor on Ilghazi and Tughtakin: a prisoner's perspective. Issue 2 (15th March 2018) - Morton, Nicholas
ABSTRACT: This article concerns two leading Turkish rulers, active in the Near East during the crusading era: Tughtakin of Damascus and Ilghazi of Mardin. They were important commanders, but the surviving sources create difficulties when outlining the contours of characters and cultural perspectives. Muslim authors typically present them as idealised Islamic rulers and yet it is difficult to accept such stereotyped portraits. This article sheds new light on these men, seeking to understand how far they had transitioned from the steppe culture of their forefathers into a more distinctively Islamic mould. It focuses in particular on the Antiochene chronicle written by Walter the Chancellor. He witnessed both rulers at first hand when he was their prisoner in Aleppo in 1119, an experience which left him deeply scarred. This is tainted evidence, yet it will be shown that many of Walter's observations also provide invaluable insights that deserve to be taken seriously.